Analisis Elastisitas Transmisi Harga Daging Ayam Ras Broiler di Tingkat Peternak dan Pasar Modern - Andarwangi, Tunjung; Pratiwi, Dita; Ulfah, Maria; Tantriadisti, Shinta (Journal of Food System & Agribusiness, 2023)
The aim of this research is to determine the elasticity of price transmission for broiler chicken meat at the farmer and modern market levels. The data used in this research is secondary data, specifically of the time series type. The analytical method used involves calculating the average price of broiler chicken meat at both the farmer and modern market levels. Subsequently, the data is analyzed using multiple regression analysis to assess the efficiency of broiler chicken meat prices. The research results indicate that the elasticity of price transmission for broiler chicken meat in this study is 2.038, which means ET > 1. This implies that a 1% increase in broiler chicken meat prices at the modern market level will result in a 2.038% change in prices at the farmer level. Therefore, the broiler chicken meat marketing system is considered inefficient.